Evaluation of Tax Compliance Supervision Policy through the issuance of a Request for Explanation of Data and/or Information (SP2DK) - Rischo Genio Septianto; Prianto Budi Saptono (Publikasi Indonesia, 2025)
This study aims to evaluate tax compliance supervision policies through the issuance of a Request for Explanation of Data and/or Information (SP2DK) with a case study approach. This research uses the theory of policy evaluation developed by William N. Dunn, which includes six dimensions of evaluation, namely effectiveness, efficiency, adequacy, fairness, responsiveness, and appropriateness. The case study used focuses on the issuance of SP2DK to PT MD for the 2020 tax year. This study identifies the challenges and successes that arise in the implementation of the SP2DK policy, as well as its impact on improving tax compliance. The results of this study are expected to provide more in-depth insight into the implementation of tax compliance supervision policies in Indonesia and provide recommendations for improving these policies.